The Tariff Act of 1930 - Taussig, F. W. (Quarterly Journal of Economics, 1930)
The final settlement; commanding position of the Conference Committee. — Higher duties on agricultural commodities, such as sugar, wheat, cotton, 3. — Hides, wool, meat, and dairy products, 7. — Minor agricultural products, 9. — Manufactured articles, cottons, woolens, silks, 13 — The general trend, 16. — The Tariff Commission retained, with no marked changes in its powers, 19.